2013
DOI: 10.1080/19338244.2013.787964
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA Damage Using 3 Comet Assay Parameters in Workers Occupationally Exposed to Lead

Abstract: The aim of this study was to investigate the association between DNA damage and blood lead levels in individuals occupationally exposed to lead. To evaluate this association, 61 workers exposed to lead were monitored in terms of DNA damage in blood lymphocytes. The levels of DNA damage were measured according to 3 comet assay parameters, including tail intensity (TI), tail moment (TM), and DNA tail (DNAt). A statistically significant positive correlation was found between the lead levels and TI, TM, and DNAt (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…These findings were consistent with previous studies using workers who exposed to arsenic (23,24).This study is also compatible with several studies that arsenic causes genotoxic effects, chromosomal abnormality, sister chromatid exchange, DNA strand breakage, oxidative DNA damage (7,23,27). Studies carried on individuals who have been exposed to various chemicals and toxicants at different occupational settings have shown that DNA damage level increases along with occupational exposure (16,(32)(33)(34)(35)(36). In contrary to these studies, we could not find a statistically significant difference between exposure time and DNA damage.…”
Section: Discussionsupporting
confidence: 82%
“…These findings were consistent with previous studies using workers who exposed to arsenic (23,24).This study is also compatible with several studies that arsenic causes genotoxic effects, chromosomal abnormality, sister chromatid exchange, DNA strand breakage, oxidative DNA damage (7,23,27). Studies carried on individuals who have been exposed to various chemicals and toxicants at different occupational settings have shown that DNA damage level increases along with occupational exposure (16,(32)(33)(34)(35)(36). In contrary to these studies, we could not find a statistically significant difference between exposure time and DNA damage.…”
Section: Discussionsupporting
confidence: 82%
“…Due to significant toxicity associated with Pb, CDC[ 5 ] has defined the standard BLL to be <10 μg/dl in adults and also has emphasized on biomonitoring in occupationally exposed workers. [ 3 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] However, it has been associated with several adverse health effects and, hence, currently has become a global health concern. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…SCGE is a technique which is low cost and sensitive; however, the published results related to smoking have, sometimes, not confirmed the damage in a convincing manner. Some authors [20, 21] state that the lack of agreement upon the methodology is the main cause of variations in the results; in addition, most use only around 3 to 5 parameters when scoring genome instability, this is in contrast to our use of 16 variables added to the PCA procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some studies have failed to find a significant difference between smokers and non-smokers using SCGE or significant association dependent on the score methods [12, 24]. On the other hand, some others have concluded that smoking can cause DNA instability when analyzed on peripheral blood cells as measured by the comet assay [21, 25]. We actually found a significant correlation with the smoking index, which has indeed been reported to have an involvement in the development of some diseases such as chronic obstructive pulmonary disease and lung cancer.…”
Section: Discussionmentioning
confidence: 99%